Using Grasping Tasks to Evaluate Hand Force Coordination in Children With Hemiplegic Cerebral Palsy - Mackenzie, Samuel J.; Getchell, Nancy; Modlesky, Christopher M.; Miller, Freeman; Jaric, Slobodan (Archives of physical medicine and rehabilitation, 2009)
Mackenzie SJ, Getchell N, Modlesky CM, Miller F, Jaric S. Using grasping tasks to evaluate hand force coordination in children with hemiplegic cerebral palsy. To assess force coordination in children with hemiplegic cerebral palsy (CP) using a device that allows for testing both unimanual and bimanual manipulation tasks performed under static and dynamic conditions. Nonequivalent groups design. University research laboratory for motor control. Six children with hemiplegic CP (age, mean ± SD, 11.6±1.8y) and 6 typically developing controls (11.6±1.6y). Not applicable. Children performed simple lifting and force-matching static ramp tasks by way of both unimanual and bimanual pulling using a device that measures grip force (force acting perpendicularly at the digits-device contact area) and load force (tangential force). Main outcome measures were grip/load force ratios (grip force scaling) and correlation coefficients (force coupling). CP subjects showed significantly higher grip/load force ratios ( P<.05) and slightly lower correlation coefficients than the control group, with more pronounced differences for most tasks when using their involved hand. For subjects with CP, switching from unimanual to bimanual conditions did not bring changes in scaling or coupling for the involved hand ( P>.05). Compared with healthy children, the impaired hand function in the hemiplegic CP pediatric population could be reflected in excessive grip force that is also decoupled from ongoing changes in load force. Therefore, the bimanual grip load device used in this study could provide a sensitive measure of grip force coordination in CP, although nonmotor deficits should be taken into account when asking children to perform more complex tasks.